1993
DOI: 10.1037/0022-3514.64.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining perceptions of control: Finding perceived control in low-control circumstances.

Abstract: Three questions about the role of perceived control in coping with a major life stressor were addressed in a sample of 71 cancer patients. As expected, those with greater perceptions of control were less depressed, even when physical functioning, marital satisfaction, and negative affectivity were controlled for. Consistent with a compensatory model of control, it was more important for patients to believe that they could control daily emotional reactions and physical symptoms than the course of the disease. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
231
4
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(251 citation statements)
references
References 20 publications
11
231
4
2
Order By: Relevance
“…For example, some time ago, Taylor, Helgeson, Reed, and Skokan (1991) showed that male medical patients who attributed control of their illness to external sources (rather than their own actions) had poorer prognoses than those who attributed such control to their own behavior and decisions. Those findings have been replicated with cancer patients (Thompson, Sobolew-Shubin, Galbraith, Schwankovsky, & Cruzen, 1993) and more recently in patients coping with chronic pain (Ramírez-Maestre, Esteve, & López, 2012). Together, these findings suggest that "internal" attributions of control over one's mental health may exert greater positive effect than "external" attributions of control, within the overall construct of resilience.…”
Section: Psychological Resiliencesupporting
confidence: 50%
“…For example, some time ago, Taylor, Helgeson, Reed, and Skokan (1991) showed that male medical patients who attributed control of their illness to external sources (rather than their own actions) had poorer prognoses than those who attributed such control to their own behavior and decisions. Those findings have been replicated with cancer patients (Thompson, Sobolew-Shubin, Galbraith, Schwankovsky, & Cruzen, 1993) and more recently in patients coping with chronic pain (Ramírez-Maestre, Esteve, & López, 2012). Together, these findings suggest that "internal" attributions of control over one's mental health may exert greater positive effect than "external" attributions of control, within the overall construct of resilience.…”
Section: Psychological Resiliencesupporting
confidence: 50%
“…8 The tool is interviewer administered and evaluates cancer patients' perception of control in low control circumstances. The 13 items yield a maximum score of 56 for perception of control and two items gave a maximum score of 14 for control over medical treatment.…”
Section: Measurementmentioning
confidence: 99%
“…Mastery, the sense that one has control of one's life, has had little attention in IBD research, despite its relevance in chronic illness [34][35][36] , and its importance to patients 37 . A person's sense of mastery or perceived control is understood to be a powerful psychological resource, with a lower sense of control negatively affecting health outcomes 38 and higher mastery associated with good mental and physical health outcomes even in the context of significant stress or health problems [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%